Penggunaan Metode Kata Lembaga untuk Meningkatkan Kemampuan Membaca Peserta Didik - Nurjanah, Nisa; Ainusyamsi, Fadlil Yani; Tantowie, Tanto Aljauhari (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2016)
This study is a classroom action research with two cycles in MIN Rajadesa Ciamis. The study succeeded in increasing the ability to read the beginning of learners through the application of methods of kata lembaga. From the aspect of early reading skills of students on an individual basis, in the first cycle only 4 learners who reach the level of completeness (40%) and the second cycle, all students have achieved mastery (100%). Additionally, the performance of teachers in the implementation of learning Indonesian by using the kata lembaga, also experienced a discernable rise from an average score of 4.12 in the first cycle to 4.88 in the second cycle.